Answer:
see explanation
Step-by-step explanation:
Given the 2 equations
3x - 5y = - 2 → (1)
2x + y = 3 → (2)
Multiply (2) by 5 will eliminate y when added to (1), that is
10x + 5y = 15 → (3)
Add (1) and (3) term by term
(3x + 10x) + (- 5y + 5y) = (- 2 + 15)
13x = 13 ( divide both sides by 13 )
x = 1
Substitute x = 1 into (2) for corresponding value of y
2 + y = 3 ⇒ y = 3 - 2 = 1
Solution is (1, 1)
|PR| = |PQ| + |QR|; |PQ| = |QR| conclusion |PR| = 2|PQ|
|PQ| = 3y; |PR| = 42; |QR|=?
subtitute
42 = 2(3y)
6y = 42 |divide both sides by 6
y = 7
|QR| = 3(7) = 21